ONLINE-BASED MATHEMATICS LEARNING VIA DRAGONLEARN IN THE COVID-19 PANDEMIC ERA - Nita Ari Rochmahdani Safitri; Muhammad Istiqlal (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2021)
The purpose of this study was to determine the process of implementing online learning via Dragonlearn Era Pandemic Covid-19. In addition to knowing the perceptions of students and teachers towards the application of online learning via Dragonlearn Era Pandemic Covid-19 and to find out the advantages and barriers to learning online via Dragonlearn Era Pandemic Covid-19. 19. This type of research uses a qualitative approach, data sources in this study include primary and secondary data sources. In the data collection technique, researchers used the method of observation, interviews, and documentation. In this study, respondents were 1 teacher and 3 students of MI Ma'had Islam Kopeng. The results of this study conclude that the process of implementing online learning via Dragonlearn Era Pandemic Covid-19 has been going well, with careful planning students can carry out learning smoothly so that teachers can evaluate through the available statistics page. Students are interested in learning like this because it produces a new learning atmosphere and many of their learning outcomes have been maximized. The teacher considers that the application of online learning via dragonlearn in the Covid-19 pandemic era has been effective because in addition to reducing the risk of the spread of Covid-19 they will also gain new experience and knowledge. The advantage is that they are more active and more confident in asking questions, they can access it anytime and anywhere. However, learning like this has obstacles that lie in the network. This learning also has disadvantages, namely that there are convoluted types of questions and the learning cannot be face-to-face so that the teacher cannot convey the material optimally.